Poly(2,3-dihexylthieno[3,4-b]pyrazine-alt-2,3-dihexylquinoxaline): Processible, Low-Bandgap, Ambipolar-Acceptor Frameworks via Direct Arylation Polymerization - Anderson, Trent E.; Culver, Evan W.; Almyahi, Furqan; Dastoor, Paul C.; Rasmussen, Seth C. (Synlett, 2018)
The synthesis of a new dialkyl-functionalized quinoxaline acceptor, 5,8-dibromo-2,3-dihexylquinoxaline, is reported, along with its cross-coupling with 2,3-dihexylthieno[3,4-b]pyrazine via direct arylation polymerization. The resulting ambipolar-acceptor polymer poly(2,3-dihexylthieno[3,4-b]pyrazine-alt-2,3-dihexylquinoxaline) exhibits a low bandgap of 1.07 eV and high solubility. The results of initial organic photovoltaic devices are also reported.
Keywords: thieno[3,4-b]pyrazine; 2,3-dihexylquinoxaline; donor–acceptor framework; low bandgap; direct arylation polymerization